A new detail for the panel zone of beam-to-wide flange column connections with endplate. (December 2021) - Solhmirzaei, Arash; Tahamouli Roudsari, Mehrzad; Hosseini Hashemi, Behrokh
Abstract: Connections are essential constituents in the behavior of a moment resisting frame. There are many different detailing schemes for steel connections, most of which involve welding. In many of these connections, it is advised to use continuity or doubler plates to improve the behavior of the panel zone. Despite enhancing the connection's behavior, using these plates is accompanied by some drawbacks, primarily due to the welding process. What this study aims to achieve is the numerical and experimental assessment of new detail for the panel zone of the beam-to-column endplates connections. In the proposed detail, the need for welding on the column in the panel zone has been thoroughly removed. A stiffened channel profile carries out the role of continuity and doubler plates. The channel is connected to the column using nuts and bolts. First, a numerical model of the proposed panel zone detail was analyzed in ABAQUS. Then, based on the numerical results, three samples were constructed and subjected to cyclic loading in a full-scale experimental setup until degradation was seen in the hysteretic diagrams. The first model was the control sample, which was built based on the specifications of the prequalified Bolted Stiffened Extended End Plate-Four Bolt Extended Stiffened (BSEEP-4ES) connection recommended by the AISC 358-16 standard. The other two samples, which were built using a channel profile with multiple stiffeners, were used as replacements for the control sample. After obtaining and evaluating the results, it was revealed that under the applied load, all three samples satisfied the seismic criteria for the special moment resistant connection. Compared to the control sample, not only did the new details exhibit a better seismic behavior, they were also more convenient to implement.